FACTORS AFFECTING RETURN ON ASSETS - Rakhman, Arif; Zakaria, Heikal Muhammad; Manda, Gusganda Suria (The International Journal of Business Review (The Jobs Review), 2019)
The objective of this research is to examine factors affecting return on assets such as cash turnover and account receivable turnover of food and beverage firm listed in Indonesia Stock Exchange. Source of data used in this study is financial statements as secondary data based on purposive sampling technique. The results showed that cash turnover does not significantly influence return on assets, this is because the value of t count is 0.558 greater than t table 2.030 so that H0 is rejected. And then, account receivable turnover significantly influence return on assets, this is based on the value of t count 5.659 is greater than t table 2.030 so H0 is accepted. And the last, The output of ANOVA results shows that the F count obtained from the variable cash turnover and accounts receivable turnover is 16.016 greater than F table 2.830 so that H0 is accepted. These results mean that there is a significant influence between cash turnover and receivable turnover on profitability in food and beverages companies listed on the Indonesian stock exchange. Based on the results, we can conclude that partially account receivable turnover was factor affecting return on assets and simultaneously cash turnover and account receivable turnover affect return on assets.